Brotherhood of the Pan - Joseph, Terry (Express)
The panyard of the Amoco Renegades Steel Orchestra devoted itself to full theatre, as the Malik Folk Performers combined with calypsonians and the host band to put on a command performance for the visiting fellow pannists of the Swiss National Steelband. The Swiss, here for the World Steelband Festival - Pan is Beautiful VIII, participated fully.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Entertainers -- Trinidad and Tobago; Musicians -- Trinidad and Tobago; Calypso (Music) -- Trinidad and Tobago